2006
DOI: 10.1128/aem.00557-06
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Metabolites Help Biocontrol Strain Pseudomonas fluorescens CHA0 To Escape Protozoan Grazing

Abstract: In soil ecosystems, bacteria must cope with predation activity, which is attributed mainly to protists. The development of antipredation strategies may help bacteria maintain higher populations and persist longer in the soil. We analyzed the interaction between the root-colonizing and biocontrol strain Pseudomonas fluorescens CHA0 and three different protist isolates (an amoeba, a flagellate, and a ciliate). CHA0 produces a set of antibiotics, HCN, and an exoprotease. We observed that protists cannot grow on C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
199
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 179 publications
(212 citation statements)
references
References 42 publications
11
199
2
Order By: Relevance
“…The strong and highly reproducible changes in the gacA-banding pattern further revealed a major shift in this master gene controlling antibiotics production of pseudomonads (De Souza et al, 2003). We suggest that pseudomonads quickly upregulated secondary metabolite production in response to protozoan predators, which is in accordance with Jousset et al (2006) who demonstrated that antibiotics of P. fluorescens are of particular toxicity to protozoa; and that antibiotic-producing P. fluorescens disproportionally benefit from protozoan predation when their bacterial competitors are consumed and nutrients excreted by the protozoan predators (Jousset et al, 2008).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The strong and highly reproducible changes in the gacA-banding pattern further revealed a major shift in this master gene controlling antibiotics production of pseudomonads (De Souza et al, 2003). We suggest that pseudomonads quickly upregulated secondary metabolite production in response to protozoan predators, which is in accordance with Jousset et al (2006) who demonstrated that antibiotics of P. fluorescens are of particular toxicity to protozoa; and that antibiotic-producing P. fluorescens disproportionally benefit from protozoan predation when their bacterial competitors are consumed and nutrients excreted by the protozoan predators (Jousset et al, 2008).…”
Section: Discussionsupporting
confidence: 70%
“…The numbers of bacteria have been shown to decline in presence of protozoa until a dynamic equilibrium with bacterial densities of 10 5 -10 7 g À1 is reached (Danso and Alexander 1975;Habte and Alexander, 1975;Acea et al, 1988;Clarholm 1981Clarholm , 1989. However, the different bacterial taxa that constitute the rhizosphere bacterial community strongly differ in their food quality for protozoa (Bjørnlund et al, 2006;Jousset et al, 2006), suggesting taxon-specific differences in bacterial survival. In fact, studies in freshwater ecosystems uncovered a number of adaptations of bacteria against protozoan grazing, such as changes in motility, size, filament formation, surface masking or toxin production to prevent ingestion, or resistance to digestion by protozoa (Jü rgens and Matz, 2002;Pernthaler, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudomonas fluorescens CHA0 is an effective colonizer of the rhizosphere of mono-and dicotyledonous plants possessing remarkable biocontrol efficiency (Voisard et al, 1994) and high resistance to predation (Jousset et al, 2006) due to the production of an array of secondary metabolites including toxins, such as hydrogen cyanide (HCN), 2,4-diacetylphloroglucinol (DAPG) and pyoluteorin (Haas et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…We used the isogenic signal-blind mutant CHA0DgacS, chromosomally tagged with green fluorescent protein 43 . This mutant lacks QS and lacks extracellular proteases required for growth on proteins 30 .…”
Section: Methodsmentioning
confidence: 99%